The influence of fluorine and its compounds on people’s health (literature review) - I. V. Donskikh (Acta Biomedica Scientifica, 2013)
The objective of this article is to analyse fluorine’s toxic effect on the health of children s population and population in general. Here are summarized the up-to-date data about the influence of natural and anthropogenic fluorine and its compounds on the health of different population groups. The researches conducted in zones of placement of aluminum productions in the Russian Federation, showed that priority specific polluting substances in the exhibited territory are compounds of the fluorine which average annual concentration make in atmospheric air of 6,2-1,4 maximum concentration limits, in the soil of 5,9-11 maximum concentration limits. The coefficient of danger of gaseous fluorine made (QH) = 1,1, risk of pathology of bone and muscular system (IH) = 1,9. It is established that compounds of fluorine get through a placenta, collect in an organism of a fruit and have toxic effect during the post-embryonic period, causing blood supply deterioration, braking of cell fission of a plate of growth of bones, easing of functional activity osteoclasts and osteoblasts, result of that is delay of growth of bones both in length, and thickness. The average levels of fluorine in biosubstrata of children living in industrial centers, above the reference sizes offered in documents of WHO. The analysis of joint action of factors of environment (lack of iodine and fluoric pollution) showed that excess intake of fluorine in an organism is one of the reasons of increase in a thyroid gland at children Thus, regardless of ways of receipt and/or influence conditions, fluorine, getting to a human body, makes toxic impact on the whole complex of bodies and systems, including cardiorespiratory, neuroendocrine, bone and muscular systems. Studying of influence of fluorine and its connections on health of the population is the important task, allowing to plan ways of prevention and correction of negative impact. Analysis of new results of researches allowed to reveal the direction of future explorations.